(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
In the learning process, the involvement and participation of all students is of great importance, which often remains incomplete when motivation is lacking. Motivation is considered a key driving force in students’ educational process, especially in the 21st century—a period of rapid change, development, and progress, where the “new generation” grows up with ideas full of challenges. It is also the era when artificial intelligence was created and is increasingly being integrated into education. This article addresses the role and importance of motivation, its external and internal factors. Examples are provided that serve as stimuli for enhancing both external and internal motivation. Some teaching strategies are presented that contribute to the increase of learners’ motivation. Finally, the article introduces various information and communication technology (ICT) tools and platforms, which not only generate interest in learning and increase students’ motivation but also help to involve weaker learners in the educational process. The impact of these tools on the effectiveness of teaching and on the growth of student motivation is also analyzed, emphasizing both the positive and negative aspects. It should be noted that the research is based on the study and analysis of both theoretical and practical sources.